User Experience Analysis of an Original Website Designed with Simplicity from the Perspective of Technology Acceptance Model - Deniz Canca; Ziya Nazım Perdahçı (Acta Infologica)
This study aims to analyze the user experience (UX) of a plainly designed website on a comprehensive subject, to determine its effect and efficiency on a target group and to find out if it is a “must” to form a detailed design for such a mission. The analysis is conducted on an original website on school preference for university selection guidance. The website differs from others by bringing in the concept of presenting comparative comments about the schools of students who studied at two different universities, with no additional information. The research is conducted by using the Technology Acceptance Model (TAM), which is based on Information Architecture (IA), for UX analyses. The info processed by relational screening technique was obtained from 256 high school students through the internet by a survey regarding their opinions about the website. Data were analyzed by Structural Equation Modeling (SEM), in the context of five hypotheses. Findings confirmed that the IA factors predicted TAM factors, which showed that such a website holds a positive effect and efficiency for the measured factors. Moreover, a result other than those estimated was also achieved, which was the absence of an effect of one of the TAM factors to another, very probably due to the design’s extreme plainness. These results present key messages both to web designers and the academy by showing that using plainness at the limits may possess extra positive outcomes and may reveal unexpected evidence in models.